2004
DOI: 10.1093/nar/gkh844
|View full text |Cite
|
Sign up to set email alerts
|

DNA adopts normal B-form upon incorporation of highly fluorescent DNA base analogue tC: NMR structure and UV-Vis spectroscopy characterization

Abstract: The influence of the highly fluorescent tricyclic cytosine base analogue (tC) on duplex DNA conformation is investigated. The duplex properties are characterized by absorbance and circular dichroism (CD) for all combinations of neighbouring bases to tC, and an NMR structure is determined for one tC-containing sequence. For the oligonucleotides with one tC incorporated instead of cytosine, the melting temperature is increased on average by 2.7 degrees C above that for the unmodified ones. CD spectra are practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
77
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 34 publications
10
77
0
Order By: Relevance
“…We have also shown that an acetic acid derivative of tC (KtC, Figure 1) exists as its normal base-pairing tautomer in the pH range 4–12 and exhibits a high fluorescence quantum yield (∼0.2) in aqueous solution (36). Previous reports have shown that tC discriminates well between A and G targets and that it thermally stabilizes DNA–DNA-, DNA–RNA-, PNA–DNA-, PNA–RNA- and PNA–PNA-duplexes (3842). The stabilization is most probably due to the improved stacking between the natural bases and the three-ring structure of tC.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have also shown that an acetic acid derivative of tC (KtC, Figure 1) exists as its normal base-pairing tautomer in the pH range 4–12 and exhibits a high fluorescence quantum yield (∼0.2) in aqueous solution (36). Previous reports have shown that tC discriminates well between A and G targets and that it thermally stabilizes DNA–DNA-, DNA–RNA-, PNA–DNA-, PNA–RNA- and PNA–PNA-duplexes (3842). The stabilization is most probably due to the improved stacking between the natural bases and the three-ring structure of tC.…”
Section: Introductionmentioning
confidence: 98%
“…The stabilization is most probably due to the improved stacking between the natural bases and the three-ring structure of tC. In a recent study we used UV-melting, circular dichroism and NMR to investigate how the exchange of cytosine for tC in DNA influences local conformation, overall structure and duplex stability (42). The study showed that incorporation of tC leaves the DNA virtually unaffected in an overall B-form and that G:tC base pairs show no increased dynamics as compared with the normal base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…1). [28][29][30][31][32][33][34][35][36] The tC nucleotide was originally developed as an analog of C with stronger binding to complementary G bases within RNA 37 and was further derivatized with a guanidinium group to form the so-called G-clamp that provides a strong binding affinity for G. [38][39][40] We find that DinB, like the Klenow fragment of DNA Pol I, can add tC triphosphate across from template dG. 28,29 We demonstrate that DinB inserts dGTP faithfully across from tC but cannot extend from the newly generated primer terminus.…”
Section: Introductionmentioning
confidence: 99%
“…1) like its sulfur-analogue tC has a negligible influence on DNA secondary structure. [10,11] Also, we have shown that tC O on average has a slightly stabilizing effect on DNA duplexes but that, with an intelligent choice of nucleobases surrounding tC O , the melting temperature can be virtually unaffected. [10] Like all other fluorescent base analogs except tC [12,13] quantum yield that is sensitive to hybridization and the nature of the surrounding bases (0.14 b ϕ f b 0.41) [10].…”
Section: Introductionmentioning
confidence: 91%